Property risk under solvency II: effects of different unsmoothing techniques - Durán Santomil, Pablo; Otero González, Luís; Martorell Cunill, Onofre; Gil-Lafuente, Anna M. (Technological and Economic Development of Economy, 2019)
Solvency II imposes risk-based capital requirements on EU insurance companies. This paper evaluates the property risk standard model proposed. The calibration was performed from the IPD UK monthly index total returns for the period between December 1986 and December 2009. In general, it is considered that returns derived from valuation-based indices are smoother than those derived from transaction-based indices. This paper contributes to the existing literature by applying various unsmoothing techniques to this index. The results show that the capital requirements, applying the same calculation method (historical value at risk at the 99.5% confidence level) as in the calibration of the standard model, are generally bigger than those proposed in the standard model of Solvency II.